(Un)-African: queering South Africas approach to SOGI rights - Berry, Neil Alexander (Department of Political Studies, 2022)
This study uses Queer Theory to explore the inconsistencies in South Africa's approach to the international protection of people of non-normative sexual orientations and gender identities (SOGI). It seeks to understand why South Africa's support for SOGI rights in the international system has been inconsistent, by answering the following question: How can we understand South Africa's inconsistent approach to sexual orientation and gender identity (SOGI) rights in the United Nations using Queer Theory? Using queer critical discourse analysis and Weber's queer logics of statecraft (Weber, 2016a; 2016b), SOGI rights discourses were studied at three levels. Firstly, the genesis of SOGI rights adoption within the post-apartheid South African policy and legislative frameworks. Secondly, providing contextual background, across the African continent since 1994. Thirdly, within dedicated SOGI debates at the UN General Assembly and UN Human Rights Council since 2011, focussing on South African and African Group contributions. This analysis determined that SOGI rights have been challenged by claims of cultural, historical and religious traditions, which on the African continent have been framed as un-African and a rejection of neocolonialism from the global North. Despite the fallacy of this un-African claim, it has impacted on South Africa as it sought to re-establish its Africanness and anti-neocolonial credentials whilst also promoting its moral leadership on human rights. It has further been established that the South African approach to SOGI rights was informed by the demands of local rather than international SOGI rights NGOs. This approach has disappointed those who anticipate the Western model of SOGI rights promotion, which South Africa has critiqued for its coercive and counter-productive punitive measures. By using Queer Theory, this study concluded that South Africa's identity can be understood beyond monolithic binaries, that South Africa's support for SOGI rights in the UN has endeavoured to find a balance between the competing aims of SOGI rights and African solidarity by presenting itself as an African and/or un-African state. This study contributes to the emerging Queer Theory literature within International Relations and to literature on queer African sexualities and genders, human rights, and foreign policy.